Composite phosphate-coated high-voltage sodium electric layered oxide positive electrode material and preparation method

CN121076112BActive Publication Date: 2026-11-03HUNAN MEITE XINCAILIAO SCI & TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511532678.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2026-11-03
Estimated Expiration
2045-10-24

AI Technical Summary

Technical Problem

High-voltage O3-type sodium-ion layered oxide cathode materials have problems with cycle stability and electrolyte erosion, leading to rapid capacity decay and exacerbated side reactions.

Method used

Alumina and NaCaAl(PO4)2 are coated on the surface of sodium-ion layered oxide cathode material to form a composite barrier that prevents the electrolyte from contacting the material and provides a fast sodium ion transport channel, enhances chemical bonding, and inhibits lattice oxygen release.

Benefits of technology

It improves the cycle stability and capacity of the material, reduces battery gas production and volume expansion rate, and enhances the cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121076112B_ABST
    Figure CN121076112B_ABST
Patent Text Reader

Abstract

The application provides a composite phosphate-coated high-voltage sodium battery layered oxide positive electrode material, which comprises a sodium battery layered oxide in the interior of the material and a coating layer coated on the surface of the sodium battery layered oxide, and the material of the coating layer comprises aluminum oxide and NaCaAl (PO4) 2. The composite phosphate-coated high-voltage sodium battery layered oxide positive electrode material coats aluminum oxide and NaCaAl (PO4) 2 on the surface of the sodium battery layered oxide, the Al2O3 in the composite coating layer is beneficial to the formation of a dense physical barrier to block the direct contact of the electrolyte with the positive electrode material, the NaCaAl (PO4) 2 coating layer is chemically bonded to the matrix through P-O bonds to inhibit HF corrosion, the P-O-Ca bonds in the NaCaAl (PO4) 2 strengthen the chemical bonding of the coating layer and the matrix to inhibit the peeling of the coating layer, and Ca 2+ forms a lattice distortion with Al 3+ (0.54 Å), relieves the volume change in charging and discharging, reduces the volume expansion rate in the cycle of the battery material, and improves the capacity and cycle performance of the composite phosphate-coated high-voltage sodium battery layered oxide positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to sodium battery materials, specifically to a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material and its preparation method. Background Technology

[0002] High-voltage O3-type sodium-electric layered oxides (such as NaNi) x Fe y Mn z O2 (oxygen dioxide) is considered a core material for next-generation power batteries due to its high theoretical specific capacity (>200 mAh / g) and low cost. However, its commercialization faces the following key challenges: Poor cycle stability: During high-voltage (>4.0V) cycling, irreversible phase transition reactions occur due to the dissolution of transition metals within the material, leading to the enrichment of oxygen vacancies on the material surface and resulting in rapid capacity decay (retention rate <80% after 200 cycles). Severe electrolyte corrosion: Under high cutoff voltage, residual alkali (such as Na2CO3) in the layered structure reacts with the electrolyte to generate HF, accelerating interfacial side reactions, triggering gas evolution and SEI film damage. Summary of the Invention

[0003] The purpose of this invention is to overcome the shortcomings of the existing technology and provide a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material and its preparation method.

[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material, wherein the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material comprises a sodium-ion layered oxide located inside the material and a coating layer coating the surface of the sodium-ion layered oxide, wherein the coating layer is made of alumina and sodium oxide. a CaAl(PO4)2, 0.7≤a≤1.1.

[0005] The inventors discovered that the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material involves coating the sodium-ion layered oxide surface with alumina and NaCaAl(PO4)2. The alumina and NaCaAl(PO4)2 work synergistically with the sodium-ion layered oxide. The Al2O3 in the composite coating layer facilitates the formation of a dense physical barrier, preventing direct contact between the electrolyte and the cathode material. The NaCaAl(PO4)2 coating layer provides a rapid sodium ion transport channel. Simultaneously, the PO-Ca bonds in NaCaAl(PO4)2 enhance the chemical bonding between the coating layer and the substrate, suppressing lattice oxygen release. After combining with Al2O3, gas generation during battery cycling is significantly reduced. 2+ (Radius 0.99Å) and Al 3+(0.54 Å) Lattice distortion occurs. The composite coating layer of alumina and NaCaAl(PO4)2 acts as a composite barrier to protect against electrolyte corrosion. It also possesses the fast-ion conductor properties of sodium ions, resulting in rapid ion transport. Furthermore, its more stable chemical structure suppresses the formation of lattice oxygen during deep oxidation reactions at high voltages, increasing stability and suppressing gas generation while ensuring further improvements in capacity and cycle life. This mitigates charge-discharge volume changes, reduces the volume expansion rate of battery materials during cycling, and improves the capacity and cycle performance of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material.

[0006] Preferably, the sodium-electric layered oxide is NaNi. x Fe y Mn z O2, x+y+z=1.

[0007] Preferably, the sodium-ionized layered oxide is NaNi. x Fe y Mn z O2, x+y+z=1 and 0.3≤x≤0.4, 0.3≤y≤0.4, 0.3≤z≤0.4.

[0008] Preferably, the sodium-ionized layered oxide is NaNi. x Fe y Mn z O2, x+y+z=1 and x=y=z=1 / 3.

[0009] Preferably, the weight of the coating layer accounts for 0.5wt% to 1.5wt% of the weight of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material.

[0010] Preferably, the weight of the coating layer accounts for 0.5wt% to 1.0wt% of the weight of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material.

[0011] The inventors discovered that when the weight of the coating layer accounts for 0.5wt% to 1.0wt% of the weight of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material, the volume expansion rate of the battery material during cycling is further reduced, thereby improving the capacity and cycle performance of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material.

[0012] Preferably, the weight ratio of NaCaAl(PO4)2 to aluminum oxide in the coating layer is 1.5~2.5:1.

[0013] The inventors discovered that when the weight ratio of NaCaAl(PO4)2 to aluminum oxide in the coating layer is 1:1.5~2.5, NaCaAl(PO4)2 and aluminum oxide achieve better compatibility, further reducing the volume expansion rate of the battery material during cycling and improving the capacity and cycle performance of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material.

[0014] Preferably, the weight ratio of NaCaAl(PO4)2 to aluminum oxide in the coating layer is 1.8~2.2:1.

[0015] Preferably, the thickness of the coating layer is 2~20 nm.

[0016] This invention also provides a method for preparing any of the above-described composite phosphate-coated high-voltage sodium-ion layered oxide cathode materials, the method comprising the following steps: (1) Disperse Al2O3, NH4H2PO4, Na2CO3, and Ca(PO3)2 in a molar ratio of (0.3~0.7):(1.5~2.5):(0.3~0.7):1 in 25 mL of a water-ethanol mixture with a volume ratio of 1:1, add 0.05wt%~0.15wt% thickener and 0.3wt%~0.8wt% sucrose as carbon source and mix well to obtain a mixed slurry; (2) Disperse the powder or granular sodium-ion layered oxide evenly in the system of step (1), stir and react at room temperature for 1.5 to 3 hours, and then filter to collect the solid. (3) After vacuum drying, the temperature is gradually increased to 450-550℃ at a rate of 15-25℃ / min and then sintered in air atmosphere for 1-2 hours. After replacing the air with inert gas, the temperature is rapidly increased to 600-800℃ at a rate of 40-50℃ / min and calcined in inert gas atmosphere for 6-10 hours.

[0017] In the preparation method of composite phosphate-coated high-voltage sodium-ion layered oxide cathode material, Al2O3, NH4H2PO4, Na2CO3, and Ca(PO3)2 are used as raw materials for NaCaAl(PO4)2. The coating layer also contains Al2O3, and 0.3wt%~0.8wt% sucrose is used as a carbon source to cover NH4. + The surface is treated to reduce oxidation loss, improve phosphorus utilization, and reduce raw material costs. The temperature is gradually increased from 15~25℃ / min to 450~550℃, then sintered in air, followed by rapid heating to 600~800℃ and calcined in an inert gas atmosphere for 6~10 hours. This gradual heating suppresses ammonia leakage and accelerates the decomposition of Ca(PO3)2.

[0018] Preferably, the pH of the mixed slurry in step (1) is 8-9, and the thickener is polyvinylpyrrolidone (PVP).

[0019] The mixed slurry coats the surface of sodium-ionized layered oxides. After calcination, a coating layer of NaCaAl(PO4)2 and alumina is formed. The pH is 8-9 to inhibit the H2O on the surface of O3-type materials. + / Na + Exchange to prevent structural collapse.

[0020] Preferably, the mixing and uniform dispersion method in steps (1) and (2) is material stirring + auxiliary ultrasound.

[0021] Preferably, in step (3), the inert gas is argon.

[0022] Preferably, the weight ratio of Ca(PO3)2 in step (1) to sodium electrolytic layered oxide in step (2) is 0.5~1.5:100.

[0023] The beneficial effects of this invention are as follows: This invention provides a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material and its preparation method. The composite phosphate-coated high-voltage sodium-ion layered oxide cathode material of this invention has aluminum oxide and NaCaAl(PO4)2 coated on the surface of the sodium-ion layered oxide. The aluminum oxide and NaCaAl(PO4)2 work synergistically with the sodium-ion layered oxide. The Al2O3 in the composite coating layer helps to form a dense physical barrier, preventing direct contact between the electrolyte and the cathode material. The NaCaAl(PO4)2 coating layer has a fast sodium ion transport channel. Simultaneously, the PO-Ca bonds in NaCaAl(PO4)2 enhance the chemical bonding between the coating layer and the matrix, suppressing lattice oxygen release. After being combined with Al2O3, gas generation during battery cycling is greatly reduced; Ca... 2+ (Radius 0.99Å) and Al 3+ (0.54Å) lattice distortion is formed, which alleviates the volume change during charging and discharging, reduces the volume expansion rate of the battery material during cycling, and improves the capacity and cycle performance of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material.

[0024] In the preparation method of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material of the present invention, Al2O3, NH4H2PO4, Na2CO3, and Ca(PO3)2 are used as raw materials for NaCaAl(PO4)2, and the coating layer also contains Al2O3, and 0.3wt%~0.8wt% sucrose is used as a carbon source to cover NH4. + The surface is treated to reduce oxidation loss, improve phosphorus utilization, and reduce raw material costs. The temperature is gradually increased from 15~25℃ / min to 450~550℃, then sintered in air, followed by rapid heating to 600~800℃ and calcined in an inert gas atmosphere for 6~10 hours. This gradual heating suppresses ammonia leakage and accelerates the decomposition of Ca(PO3)2. Attached Figure Description

[0025] Figure 1 This is a TEM image of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material of Example 1 of the present invention.

[0026] Figure 2 This is a FIB-TEM image of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material of Example 1 of the present invention.

[0027] Figure 3 The image shows the EDS image of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material of Example 1 of the present invention.

[0028] Figure 4 This is a discharge curve of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material according to an embodiment of the present invention.

[0029] Figure 5 This is a cycle capacity diagram of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material according to an embodiment of the present invention. Detailed Implementation

[0030] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0031] Example 1 As an embodiment of the present invention, a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material comprises a sodium-ion layered oxide located inside the material and a coating layer coating the surface of the sodium-ion layered oxide. The coating layer is made of alumina and NaCaAl(PO4)2, Na a CaAl(PO4)2, 0.7≤a≤1.1; Sodium-ionized layered oxide is NaNi x Fe y Mn z O2, x+y+z=1 and x=y=z=1 / 3; The coating layer accounts for 0.7 wt% of the weight of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material. The weight ratio of NaCaAl(PO4)2 to aluminum oxide in the coating layer is 2:1.

[0032] The coating thickness is 14.5 nm; As a method for preparing the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material described in this embodiment, the method includes the following steps: (1) Disperse Al2O3, NH4H2PO4, Na2CO3 and Ca(PO3)2 in a water-ethanol mixed solvent at a molar ratio of 0.7:2:0.5:1, add 0.1wt% PVP thickener and 0.5wt% sucrose as carbon source and ultrasonically mix to obtain a mixed slurry. Adjust the pH of the mixed slurry to 8~9 with Na2CO3. The weight ratio of Ca(PO3)2 in step (1) to sodium electrolytic layered oxide in step (2) is 1.1:100. (2) Disperse the powdered sodium-ion layered oxide evenly in the system of step (1) and stir at 25±2℃ for 1.5~3 hours to coat the surface of the powdered sodium-ion layered oxide with the slurry of step (1), and collect the solid by filtration. (3) After vacuum drying at 80℃, the temperature is gradually increased to 500℃ at 20℃ / min and then sintered in air atmosphere for 2 hours. After argon gas is introduced for 2 minutes, the temperature is rapidly increased to 700℃ at 45℃ / min and calcined in argon gas atmosphere for 8 hours.

[0033] Example 2 As an embodiment of the present invention, a composite phosphate-coated high-voltage sodium-electric layered oxide cathode material is provided. The only difference between this embodiment and Embodiment 1 is that the weight of the coating layer accounts for 0.2 wt% of the weight of the composite phosphate-coated high-voltage sodium-electric layered oxide cathode material.

[0034] Example 3 As an embodiment of the present invention, the only difference between this embodiment and Embodiment 1 is that the weight of the coating layer accounts for 0.5 wt% of the weight of the composite phosphate-coated high-voltage sodium-electric layered oxide cathode material.

[0035] Example 4 As an embodiment of the present invention, a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material is described. The only difference between this embodiment and Embodiment 1 is that the weight of the coating layer accounts for 1.0 wt% of the weight of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material.

[0036] Example 5 As an embodiment of the present invention, a composite phosphate-coated high-voltage sodium-electric layered oxide cathode material is described. The only difference between this embodiment and Embodiment 1 is that the weight of the coating layer accounts for 1.2 wt% of the weight of the composite phosphate-coated high-voltage sodium-electric layered oxide cathode material.

[0037] Example 6 As a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material of this invention, the only difference between this embodiment and Example 1 is that the weight ratio of NaCaAl(PO4)2 to aluminum oxide in the coating layer is 10:1.

[0038] Example 7 As a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material of this invention, the only difference between this embodiment and Example 1 is that the weight ratio of NaCaAl(PO4)2 to aluminum oxide in the coating layer is 10:2.

[0039] Example 8 As a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material of this invention, the only difference between this embodiment and Example 1 is that the weight ratio of NaCaAl(PO4)2 to aluminum oxide in the coating layer is 10:4.

[0040] Example 9 As a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material of this invention, the only difference between this embodiment and Example 1 is that the weight ratio of NaCaAl(PO4)2 to aluminum oxide in the coating layer is 10:15.

[0041] Example 10 As a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material of this invention, the only difference between this embodiment and Embodiment 1 is that the sodium-ion layered oxide is NaNi. x Fe y Mn z O2, x+y+z=1 and x=0.28, y=0.35, z=0.37.

[0042] Comparative Example 1 As a comparative example of the present invention, this high-voltage sodium-ion layered oxide cathode material with composite phosphate coating is the only difference between this comparative example and Example 1: the coating layer is aluminum oxide.

[0043] Comparative Example 2 As a comparative example of the present invention, a composite phosphate-coated high-voltage sodium-ion layered oxide cathode material, the only difference between this comparative example and Example 1 is that the molar ratio of Al2O3, NH4H2PO4, Na2CO3, and Ca(PO3)2 is 0.5:2:0.5:1, and the coating layer is NaCaAl(PO4)2.

[0044] I. Experimental Methods (I) Material Characterization like Figure 1 The image shows a TEM image of Example 1. It can be clearly seen from the image that there is an obvious nano-coating layer on the surface of the substrate, with a thickness ranging from a few nanometers to 20 nanometers.

[0045] Figure 2The image shown is a FIB-TEM image of Example 1. After the material is cut crosswise, obvious coating marks can be seen on the edges of the particles.

[0046] Figure 3 The EDS image of SEM in Example 1 shows that the particles are uniformly coated with each element with obvious coating element signals. The maximum intensity of the coating element signals is Al > P > Ca, which is consistent with the element content ratio of the Al2O3+ NaCaAl(PO4)2 composite coating layer.

[0047] (ii) Cyclic volume expansion rate The volume expansion rate during cycling was tested using a dedicated coin cell in-situ expansion test system, model RSS1400, and a single-electrode expansion test mold. The mold is equipped with a ceramic diaphragm to isolate the lithium electrode from its influence.

[0048] (III) Battery performance testing Test Method: The positive electrode materials obtained in Examples 1-10 and Comparative Examples 1-2 were used as active materials. They were mixed at a mass ratio of active material: conductive agent (Super P): binder (PVDF) of 90:5:5. An appropriate amount of NMP solvent was added to adjust the solid content. The mixture was stirred into a slurry using a pulping machine and then coated onto aluminum foil. After coating, the electrode sheets were dried in an oven at 110°C for 4 hours. Using sodium foil as the negative electrode, glass fiber as the separator, and 1M NaPF6 (solvent EC:DEC = 1:1 Vol%) as the electrolyte, coin cells were assembled in a glove box. The cells were tested at room temperature within a voltage range of 2.0–4.15V, activated at 0.1C for two weeks, and then subjected to a 200-cycle cycle test at 0.5C.

[0049] The composite phosphate-coated high-voltage sodium-ion layered oxide cathode materials prepared in Examples 1-10 and Comparative Examples 1-2 are used.

[0050] Table 1

[0051] As shown in Table 1, the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material of this invention has aluminum oxide and NaCaAl(PO4)2 coated on the surface of the sodium-ion layered oxide. The aluminum oxide and NaCaAl(PO4)2 work synergistically with the sodium-ion layered oxide. The Al2O3 in the composite coating layer helps form a dense physical barrier, preventing direct contact between the electrolyte and the cathode material. The NaCaAl(PO4)2 coating layer has a fast sodium ion transport channel. Simultaneously, the PO-Ca bonds in NaCaAl(PO4)2 enhance the chemical bonding between the coating layer and the substrate, suppressing lattice oxygen release. After being combined with Al2O3, gas generation during battery cycling is significantly reduced. 2+ (Radius 0.99Å) and Al 3+(0.54Å) lattice distortion is formed, which alleviates the volume change during charging and discharging, reduces the volume expansion rate of the battery material during cycling, and improves the capacity and cycle performance of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material.

[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A composite phosphate-coated high-voltage sodium-ion layered oxide cathode material, characterized in that, The composite phosphate-coated high-voltage sodium-ion layered oxide cathode material comprises a sodium-ion layered oxide located inside the material and a coating layer covering the surface of the sodium-ion layered oxide. The coating layer is made of alumina and sodium oxide. a CaAl(PO4)2, 0.7≤a≤1.1; Sodium-ionized layered oxide is NaNi x Fe y Mn z O2, x+y+z=1 and x=y=z=1 / 3; The coating layer accounts for 0.5 wt% to 1.0 wt% of the weight of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material. The weight ratio of NaCaAl(PO4)2 to alumina in the coating layer is 1.5~2.5:1; The thickness of the coating layer is 2~20 nm; The preparation method of composite phosphate coated high voltage sodium layered oxide cathode material includes the following steps: (1) Al2O3, NH4H2PO4, Na2CO3, and Ca(PO3)2 are dispersed in 25 mL of a mixed solution of water-ethanol volume ratio 1:1 at a molar ratio of (0.3~0.7):(1.5~2.5):(0.3~0.7):1, and 0.05wt%~0.15wt% thickener and 0.3wt%~0.8wt% sucrose are added as carbon source and mixed to obtain a mixed slurry; (2) Disperse the powdered or granular sodium-ionized layered oxide evenly in the system of step (1), stir and react at 25~30℃ for 1.5~3 hours, and then filter to collect the solid. (3) After vacuum drying, the temperature is gradually increased to 450-550℃ at a rate of 15-25℃ / min and then sintered in air atmosphere for 1-2 hours. After replacing the air with inert gas, the temperature is rapidly increased to 600-800℃ at a rate of 40-50℃ / min and calcined in inert gas atmosphere for 6-10 hours.

2. The composite phosphate-coated high-voltage sodium-ion layered oxide cathode material according to claim 1, characterized in that, The weight of the coating layer accounts for 0.7wt% to 1.0wt% of the weight of the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material.

3. The composite phosphate-coated high-voltage sodium-ion layered oxide cathode material according to claim 1, characterized in that, The weight ratio of NaCaAl(PO4)2 to alumina in the coating layer is 2~2.5:

1.

4. The method for preparing the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material as described in any one of claims 1 to 3, characterized in that, The method includes the following steps: (1) Disperse Al2O3, NH4H2PO4, Na2CO3, and Ca(PO3)2 in a molar ratio of (0.3~0.7):(1.5~2.5):(0.3~0.7):1 in 25 mL of a water-ethanol mixture with a volume ratio of 1:

1. Add 0.05wt%~0.15wt% thickener and 0.3wt%~0.8wt% sucrose as carbon source and mix well to obtain a mixed slurry; (2) Disperse the powdered or granular sodium-ionized layered oxide evenly in the system of step (1), stir and react at 25~30℃ for 1.5~3 hours, and then filter to collect the solid. (3) After vacuum drying, the temperature is gradually increased to 450-550℃ at a rate of 15-25℃ / min and then sintered in air atmosphere for 1-2 hours. After replacing the air with inert gas, the temperature is rapidly increased to 600-800℃ at a rate of 40-50℃ / min and calcined in inert gas atmosphere for 6-10 hours.

5. The method for preparing the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material according to claim 4, characterized in that, The pH of the mixed slurry in step (1) is 8-9, and the thickener is polyvinylpyrrolidone (PVP). The mixing and uniform dispersion methods in steps (1) and (2) are physical stirring combined with ultrasonication. In step (3), the inert gas is argon.

6. The method for preparing the composite phosphate-coated high-voltage sodium-ion layered oxide cathode material according to claim 4, characterized in that, In step (1), the weight ratio of Ca(PO3)2 to sodium electrolytic layered oxide in step (2) is 0.5~1.5:100.

Citation Information

Patent Citations

  • Composite coated high-nickel polycrystalline positive electrode material and preparation method thereof

    CN115528221A

  • Ultrahigh nickel layered oxide positive electrode material with multi-component composite structure, preparation method of ultrahigh nickel layered oxide positive electrode material and lithium ion battery

    CN117374273A

  • High-voltage positive electrode material and preparation method thereof, positive plate and sodium ion battery

    CN119133402A

  • Sodium-ion battery positive electrode material and preparation method thereof, positive electrode plate, battery and electric device

    CN119208548A

  • Modified layered oxide positive electrode material and preparation method and application thereof

    CN120015784A